Framing Social Inclusion in Nepal’s Bureaucracy: A Critical Discourse Analysis - Mijar, Madhu; Giri, Bishnu (NPRC Journal of Multidisciplinary Research, 2025)
Nepal’s constitutional mandates for social inclusion contrast sharply with persistent bureaucratic exclusion of marginalized groups such as Dalits, Janajatis, Madhesis, and women. Despite affirmative action policies such as the 2007 Civil Service Act (45% reservation), dominant caste elites retain 72% of senior bureaucratic positions, while Dalits occupy only 5.9% against a 9% quota. Employing Critical Discourse Analysis (CDA), this study interrogates how bureaucratic language, media narratives, and policy frameworks sustain exclusion under the guise of creamy layer, meritocracy and efficiency. Analyzing policy documents, interviews, and media texts, the research reveals three mechanisms of exclusion: (1) gatekeeping through "technical" recruitment classifications, (2) judicial and media framing of reservations as "reverse discrimination," and (3) symbolic policy compliance without substantive power redistribution. Findings highlight intersectional barriers e.g., Dalit women facing compounded discrimination and bureaucratic resistance, evidenced by 78% of quota-elected women being proxy-controlled by male relatives. The study critiques Nepal’s inclusion paradigm as liberal multiculturalism that prioritizes recognition over redistribution, reinforcing caste-class hierarchies. It proposes transformative pathways: intersectional quotas, an Independent Inclusion Regulator, media democratization, and land-caste justice. The conclusion underscores that without dismantling structural inequalities, inclusion policies risk remaining symbolic, perpetuating exclusion while appearing progressive. This research contributes to global debates on bureaucratic resistance to social justice and the limits of affirmative action in post-conflict states.